Makna dalam Lirik Lagu “Paris Berantai” karya Anang Ardiansyah - Yuwana Yuwana; Dwi Wahyu Candra Dewi (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This article explores the significance found in the lyrics of the song "Paris Berantai" by Anang Ardiansyah through Paul Ricoeur's hermeneutic approach. This song is among the plethora of traditional Banjar music that not only provides enjoyable melodies but also incorporates social imagery that mirrors the values of Banjar society, including love, yearning, struggle, identity, and social dynamics. The methodology employed is qualitative descriptive with hermeneutic research methods, which involve a thorough interpretation of song lyrics as social works. This research seeks to uncover the implications within the lyrics that musically and artfully express the intricacies of local culture. The findings reveal that this song is not merely a traditional musical composition but also serves as a medium for conveying the character and intellect of Banjar society. This analysis indicates that each lyric of the song holds a philosophical significance that reflects the perspectives of the Banjar people on time, social relationships, nature, and the impact of external societies. Furthermore, this song portrays the experience of profound love and acts as a channel for conveying moral, spiritual, and social messages within a sophisticated context.